Morbidity and functional mid-term outcomes using the Prolift pelvic floor repair systems - Kozal, Sébastien; Ripert, Thomas; Bayoud, Younes; Menard, Johan; Nicolacopoulos, Ioannis; Bednarzyck, Laurence; Staerman, Frederic; Larre, Stéphane (Canadian Urological Association Journal, 2014)
Introduction: We assess midterm morbidity and functional outcomes using the Prolift (Gynecare/Ethicon, Somerville, NJ) system and identify potential related risk factors. The Prolift mesh system to treat genital prolapse was introduced in 2005. It was withdrawn from the market in early 2013 after rising doubts about safety. Methods: Over a 7-year period, we retrospectively analyzed a cohort of 112 consecutive patients who underwent the Prolift procedure since 2006. Intraoperative and postoperative complications, anatomical and functional outcomes were recorded. Results: The median follow-up was 49.5 months (range: 16-85). The mean age was 64.7 ± 10.9 years (range: 40-86). Of the 112 patients, 74 patients had stage 3 (66.1%) and 8 patients had stage 4 (7.14%) vaginal prolapse. Prolift surgery was performed for prolapse recurrence for 26 patients (23.2%). Total mesh was used in 32 patients (29%), an isolated anterior mesh in 57 patients (51%) and an isolated posterior mesh in 23 patients (21%). Concomitant surgical procedures were performed for 44 patients (39.3%). Overall, 72% (18/25) of the complications were managed medically. We reported a failure rate of 8% (n = 9) occurring after a median follow-up of 9.5 months (range: 1-45). Among the 64 patients who had preoperative sexual activity (57.1%), de novo dyspareunia occurred in 9 patients (16.07%). We extracted predictive factors concerning failure, complications and sexuality. Conclusion: Despite its market withdrawal, the Prolift system was associated with good midterm anatomic outcomes and few severe complications. Long-term follow-up data are still lacking, but surgeons and patients may be reassured.